Indivíduos com doenças genéticas raras que afetam o desenvolvimento esquelético: vulnerabilidade aos problemas bucais - Flavia Rabello (2021)
Rare diseases have a wide variability of signs and symptoms. Mucopolysaccharidoses (MPS) and Osteogenesis Imperfecta (OI) are rare genetic diseases that affect skeletal development. The individuals can present craniofacial malformations, occlusal and dental changes. Physical and motor disabilities can make oral hygiene difficult. In addition to the difficulty of accessing dental care, which can make them more vulnerable to oral problems. The objective of the research was to compare Brazilian individuals with rare genetic diseases that affect skeletal development and individuals without rare diseases in relation to the prevalence of oral problems. Also, verify the feasibility of correcting the malocclusion in individuals with OI. The thesis includes the presentation of two scientific articles, a cross-sectional study and a systematic review. Article 1 aimed to compare the prevalence of oral problems in Brazilians with rare genetic diseases that affect skeletal development and individuals without rare diseases. Was performed a cross-sectional study, paired by age and sex, with 210 individuals [105 with rare genetic disease: MPS (n = 27) / OI (n = 78) and 105 individuals without rare disease], aged from two to 57 years and parents/guardians. The group with rare diseases was recruited from medical clinics of specialized or reference services in rare genetic diseases in five Brazilian states (CE, ES, MG, RJ and SP). Those without a rare disease were recruited from other outpatient clinics in the same hospitals. The groups were examined for malocclusion, dental anomalies, tooth decay and gingivitis. Parents/guardians answered a questionnaire on the individual, sociodemographic, behavioral, medical and dental history of subjects with and without rare disease. Directed Acyclic Graph was used to identify possible confounding variables. The study was approved by CEP / UFMG (CAAE 01480212.4.0000.5149 [MPS] / CAAE 54755516.4.0000.5149 [OI]). Descriptive analysis and unadjusted and adjusted binary logistic regression models (Odds Ratio, Conditional Backward method, 95%CI) were performed. The average age of the individuals examined was 14.2 years (± 12.3). The variables genetic disease, skin color and family income remained in the final model. Only the rare genetic disease has been associated with oral problems. Individuals with rare genetic diseases have 12.9 times more likely to have an oral problem (95%CI 3.7-44.7) compared to individuals without a rare disease. It was concluded that individuals with rare genetic diseases have a higher prevalence of oral problems when compared to individuals without rare genetic disease. Article 2 aimed to verify the feasibility of correcting malocclusion in individuals with OI. The search in databases identified 22 articles, covering 28 clinical cases. Malocclusion was considered severe in 11 cases, with negative overjet recordings between 9 and 26 mm. Orthodontic treatment was performed in four cases, orthognathic surgery in five, and orthodontic treatment associated with orthognathic surgery in 19 cases. It was concluded that the treatment of malocclusions is feasible in individuals with OI. When appropriately indicated, the treatment can provide satisfactory aesthetic results and adequacy and with adequate stability.